2020
DOI: 10.1371/journal.pone.0228699
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy & safety of Carica papaya leaf extract (CPLE) in severe thrombocytopenia (≤30,000/μl) in adult dengue – Results of a pilot study

Abstract: Severe thrombocytopenia in dengue often prompts platelet transfusion primarily to reduce bleeding risk. In India, about 11-43% of dengue patients report receiving platelet transfusions which is considered scarce and expensive especially in resource limited settings. Herein, we evaluated the efficacy and safety of Carica papaya leaf extract (CPLE) in the management of severe thrombocytopenia (�30,000/μL) in dengue infection. 51 laboratory confirmed adult dengue patients with platelet counts �30,000/μL were rand… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
20
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(27 citation statements)
references
References 23 publications
(25 reference statements)
2
20
0
Order By: Relevance
“…It therefore could prevent the complications of thrombocytopenia [ 94 ], and shorten the length of hospital stay in these patients [ 95 ]. Similar outcomes were also reported by a recent study [ 96 ] that also showed C. papaya treatment reduced plasma tumor necrosis factor-α, interferon-γ, and interleukin-6 as well as mean dengue non-structural protein 1 (NS1). The findings confirmed the immunomodulatory property of the plant seen in the animal study.…”
Section: Pharmacologically Active Medicinal Plants and Isolated Cosupporting
confidence: 88%
“…It therefore could prevent the complications of thrombocytopenia [ 94 ], and shorten the length of hospital stay in these patients [ 95 ]. Similar outcomes were also reported by a recent study [ 96 ] that also showed C. papaya treatment reduced plasma tumor necrosis factor-α, interferon-γ, and interleukin-6 as well as mean dengue non-structural protein 1 (NS1). The findings confirmed the immunomodulatory property of the plant seen in the animal study.…”
Section: Pharmacologically Active Medicinal Plants and Isolated Cosupporting
confidence: 88%
“…In vitro antiviral activity of Irvingia gabonensis extract against human immunodeficiency virus (HIV) has been reported (Abdurahman et al, 1995). In vitro and pilot study have reported antiviral activity of Carica papaya leaves aqueous extract against dengue virus (Sathyapalan et al, 2020;Sharma et al, 2019;Joseph et al, 2015), through inhibition of the viral non-structural 2B and 3 (NS2B-NS3) protease complex which is crucial for virus replication (Senthilvel et al, 2013) and this is similar to the mechanism reported for simeprevir (Verbinnen et al, 2015) and clemizole (Einav et al, 2008). Carica papaya and Corchorus olitorius have been used to treat asthma properties in Nigerian traditional medicine (Erinoso & Aworinde, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Apart from increase in the thrombocyte, the study also suggested the improvement of the symptoms in dengue might due to the anti-hemolytic activity of papaya too [12] . In another study by Sathyapalan et al (2020), the patients with severe thrombocytopenia who has taken 1100 mg of papaya leaf extract in tablet three times a day for 5 days showed an increase in the platelet count in the first 4 days and then the platelet count is maintained on day 5 compared to the placebo group in which the platelet count increases slowly and the platelet count drops on day 5. This indicates that the Carica papaya leaf extract has the capability to maintain the platelet count where it promotes the production of platelets and could be used in severe condition, thus proving the reliability as an alternative treatment for dengue patients [24] .…”
Section: Anti-thrombocytopenic Effect Of Carica Papayamentioning
confidence: 96%
“…Research have been done to investigate the beneficial effect of papaya leaf extract as an immune-boosting impact to the dengue patients. A study by Sathyapalan et al (2020) proposed that oral administration of 1100 mg of papaya leaf extract in tablet three times a day for 5 days in human has initiated and activated the coagulation and inflammation pathways lead to the release of proinflammatory cytokines such as TNG-alpha, IFN-gamma and IL-6, that further inhibit the thrombocytopenia in patients [24] . Similarly, another research team has proposed that the unripe papaya leaf juice extract (10% v/v) which consists of major compound papain, may enhance IL-6 secretion and lead to the proliferation, maturation and differentiation of multipotential heamatopoietic progenitors and then increase in thrombocyte production in mesenchymal stem cells and haematopoietic cells.…”
Section: Immunomodulatory Effect Of Carica Papayamentioning
confidence: 99%